The Role of Artificial Intelligence in Business Value Creation: The Mediating Role of Organizational Capability in Small and Medium Enterprises (SMEs) - Indira Oralas; Ika Puji Rahayu; Iwan Virgo Irawan; Rini Siva Aulia (Lentera Ilmu Madani, 2026)
This paper discusses the impact of artificial intelligence on business value formation. Organizational capability is considered as a mediator in this case in terms of small and medium enterprises. The research seeks to examine artificial intelligence, decision-making capability, and innovation capability impacts on organizational capability. Further, the impact of organizational capability on business value is analyzed in this study. Quantitative research methodology was adopted, with data gathered from a sample of 76 respondents employed by small and medium enterprises. This data was analyzed using descriptive statistics, reliability analysis, and multiple regression analysis. The findings reveal that decision-making has a statistically significant effect on organizational capability; however, artificial intelligence and innovation capability do not have any significant direct effects. At the same time, organizational capability has a high statistically significant effect on business value formation. According to these results, it can be said that managerial capabilities play a greater role in organizational capability formation compared to technological and innovation capabilities. In other words, it is internal capabilities of organizations and proper management of resources rather than artificial intelligence that matter most when creating business value.